Improving MSME Competitiveness through Visual Design and Digital Branding Training - Suryari Purnama; Felix Sutisna; Ninda Lutfiani; Dimas Aditya Prabowo; Syahyono Syahyono (ADI Pengabdian Kepada Masyarakat, 2026)
The strategic role of visual design and digital branding training in enhancing the competitiveness of micro, small, and medium enterprises (MSMEs) has become increasingly important in the digital economy era. Many MSMEs still face limitations in market reach and weak brand identity due to inadequate visual communication skills and minimal implementation of digital branding strategies. These challenges reduce their competitiveness in an increasingly competitive online marketplace. This community service program aims to analyze the impact of structured training in visual design and digital branding on improving brand perception, market visibility, and sales performance of MSMEs. This program employs a mixed-method approach by combining pre-test and post-test surveys, in-depth interviews, and direct observation. The participants consisted of 50 MSME actors who took part in a a three-month training program covering logo design, product packaging, social media branding, and digital marketing content creation. Quantitative data were analyzed using paired statistical tests, while qualitative data were examined through thematic analysis. The results indicate a significant improvement in brand consistency, visual attractiveness, digital engagement, and online sales growth after the participants completed the training program. Participants also reported increased confidence in managing brand assets and implementing digital communication strategies. It can be concluded that visual design and digital branding training represent an effective intervention to strengthen the competitiveness of MSMEs, support sustainable business growth, and promote the development of a resilient creative economy in the era of digital transformation.